FROM REGULATION TO PRACTICE: EMPIRICAL EVIDENCE ON THE ROLE OF SHARIA SUPERVISORY BOARDS IN INDONESIAN ISLAMIC BANKS - Yulia Hafizah; Muhammad Rifqi Hidayat (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2026)
Although the DPS plays an important role in ensuring Sharia compliance in Islamic banking, empirical research on the regulations governing the DPS and how they are implemented in concrete supervision at the bank level is still limited. This study aims to analyse the duties and functions of the DPS in practice at Islamic banks in Indonesia. The research uses qualitative methods and analysis techniques with a case study approach, alongside interviews and regulatory documents as data collection methods. Research results show that DPS according to regulations has at least four tasks that must be carried out technically, namely supervising the issuance of new bank products in the form of sharia opinion documents and supervisory working papers on the new bank product development process; conducting inspections on existing products; holding routine meetings at least once a month which are recorded in the self-assessment documents in the bank's GCG report; and signing the bank's financial statements if it is still in the form of a sharia business unit. This research contributes to regulators, such as OJK and DSN, to ensure regulations related to DPS are implemented in practice.